2020
DOI: 10.1002/hed.26360
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous carcinoma: Aggressive tumor pattern of invasion predicts direct mandible invasion

Abstract: Background: Aggressive histologic worst pattern of invasion (WPOI) in surrounding soft tissue has been shown to be predictive of higher local recurrence and poorer survival in oral cavity squamous cell carcinoma (OCSCC) patients. This study investigates whether aggressive WPOI can predict the mandibular invasion phenotype. Methods: Patients consecutively diagnosed with OCSCC undergoing a mandibulectomy (marginal or segmental) between 2013 and 2018 were reviewed. Senior physicians re-reviewed radiologic scans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
8
0
2
Order By: Relevance
“…[30][31][32] According to Yue et al, the pattern of soft-tissue invasion has become a useful tool that further characterizes the biologic behavior of OCSCC. 33 The authors concluded that an aggressive histologic worst pattern of invasion in OCSCC tumors exhibited an infiltrative pattern of mandibular invasion too. 33 In the same vein, researchers have shown that, at the beginning, bone erosion occurs as a result of osteoclast cell activity at the frontline of tumor infiltration, probably related to the inflammation process and before bone invasion by tumor cells.…”
Section: Discussionmentioning
confidence: 98%
“…[30][31][32] According to Yue et al, the pattern of soft-tissue invasion has become a useful tool that further characterizes the biologic behavior of OCSCC. 33 The authors concluded that an aggressive histologic worst pattern of invasion in OCSCC tumors exhibited an infiltrative pattern of mandibular invasion too. 33 In the same vein, researchers have shown that, at the beginning, bone erosion occurs as a result of osteoclast cell activity at the frontline of tumor infiltration, probably related to the inflammation process and before bone invasion by tumor cells.…”
Section: Discussionmentioning
confidence: 98%
“…Histologically, OSCC tends to be well or moderately differentiated, characterized by cells with higher and eosinophilic cytoplasm, round nuclei with mild hyperchromasia and desmosomes, areas of dyskeratosis and horny pearls have been observed. Whereas poorly differentiated OSCCs that occur less frequently, exhibit greater cellular atypia and loss of squamous characteristics, therefore, immunohistochemical analysis must sometimes be performed for confirmation of their diagnosis 19 , 20 ,…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, há ainda a dor somática, causada pela fixação da tela por suturas ou grampos, que podem atingir o periósteo mais profundamente, gerando uma periostite. 3,18 Por fim, tem-se a dor visceral, que está relacionada a danos ao intestino, cordão espermático ou estruturas periuretrais.…”
Section: Discussionunclassified
“…Dentre os subtipos conhecidos do carcinoma de células escamosas, o Carcinoma verrucoso é caracterizado por crescimento exofítico com fronte de invasão expansiva e atipias celulares mínimas, sendo considerado de bom prognóstico e não-metastatizante (ainda que possa progredir para ou coexistir com um CEC convencional) (18).…”
Section: Discussionunclassified